Appendiceal Carcinoid Tumor within Amyand's Hernia: A Case Report and - Sarici, B; Akbulut, S; Piskin, T (2019)
Introduction: Amyand's hernia is defined as the herniation of the whole or a part of appendix vermiformis into an inguinal hernia sac. Amyand's hernia is very rare, constituting about 1% of all inguinal hernia patients and 0.1% of all acute appendicitis patients. In one-quarter of Amyand's hernia patients, inflammatory changes are detected in appendix vermiformis. Detecting an appendiceal tumor in an Amyand's hernia sac is extremely rare, with only eight cases having been reported so far in the English literature. Case presentation: A 64-year-old man with an appendiceal carcinoid tumor inside an incarcerated Amyand's hernia sac. As the tumor was localized to the radix of the appendix, resection was carried out with the help of a linear-cutter stapler in a way to contain a part of the cecal wall. As the pathology examination revealed a carcinoid tumor infiltrating the periappendicular fatty tissue, right hemicolectomy was performed in a second session, in compliance with the oncological principles. No metastasis was present at the 24th month. Case reports published in the English literature regarding the Amyand's hernia with an appendiceal tumor were also analyzed in this study. Conclusion: Amyand's hernia containing an appendiceal tumor is an extremely rare clinical entity. Clinical manifestations mostly mimic the incarcerated hernia and thus accurate diagnosis is made incidentally during hernia surgery. The basic oncological principles apply for the approach to tumors inside a hernia sac. C1 [Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. Inonu Univ, Fac Med, Liver Transplant Inst, TR-44280 Malatya, Turkey.